1999
DOI: 10.1115/1.1303703
|View full text |Cite
|
Sign up to set email alerts
|

Flowfield Measurements in the Endwall Region of a Stator Vane

Abstract: A first-stage stator vane experiences high heat transfer rates, particularly near the endwall, where strong secondary flows occur. In order to improve numerical predictions of the complex endwall flow at low-speed conditions, benchmark quality experimental data are required. This study documents the flowfield in the endwall region of a stator vane that has been scaled up by a factor of nine while matching an engine exit Reynolds number of Reex=1.2×106. Laser Doppler velocimeter (LDV) measurements of all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Endwall heat transfer can behave differently compared to a vane surface because of the presence of strong external secondary flows, namely the horseshoe and passage vortices. The passage vortices affect the endwall by skewing the direction of endwall flow and locally increasing the external heat transfer coefficients as shown by Kang and Thole [7]. The first experimental study for a conjugate endwall exposed to passage flows was completed by Mensch and Thole [2].…”
Section: Relevant Literaturementioning
confidence: 99%
“…Endwall heat transfer can behave differently compared to a vane surface because of the presence of strong external secondary flows, namely the horseshoe and passage vortices. The passage vortices affect the endwall by skewing the direction of endwall flow and locally increasing the external heat transfer coefficients as shown by Kang and Thole [7]. The first experimental study for a conjugate endwall exposed to passage flows was completed by Mensch and Thole [2].…”
Section: Relevant Literaturementioning
confidence: 99%
“…The external heat transfer for an endwall differs from that of a flat plate, leading edge or airfoil surface, due to the influence of passage secondary flows including the horseshoe and passage vortices. The passage vortices that develop along the endwall skew the direction of endwall flow and locally increase the external heat transfer coefficient, as measured by Kang and Thole [21]. The distribution of the external endwall heat transfer coefficients for the airfoil geometry in this study was investigated by Lynch et al [22] through both experiments and computational predictions with a constant wall heat flux boundary condition.…”
Section: Relevant Literaturementioning
confidence: 75%
“…Most research conducted under unsteady flow conditions focused on the combustor exit flow field and its influence on the aerothermal turbine performance. 85 Kerrebrock and Mikolajczak 86 described the positive/negative jet effects generated by the nonuniform turbine inlet pressures, temperature fields, and the relative motion of the stator and rotor blades. Ong and Miller 87 and Sipatov et al 79 observed the mechanism of redistribution of hot and cold gas regions in the rotor passage.…”
Section: Unsteady Convective Heat Transfer Modelmentioning
confidence: 99%